1998
DOI: 10.1097/00006534-199806000-00018
|View full text |Cite
|
Sign up to set email alerts
|

Advantage of the Presence of Living Dermal Fibroblasts within in Vitro Reconstructed Skin for Grafting in Humans

Abstract: Methods for serial cultivation of human keratinocytes can provide large quantities of epidermal cells, which have the potential of restoring the vital barrier function of the epidermis in extensive skin defects such as burns. To investigate the value of combining an epidermis with a dermal component, fibroblasts originated from the superficial dermis were used to seed a collagen lattice as described by E. Bell (dermal equivalent). Beginning in 1981, we grafted 18 patients (burns and giant nevi) using 35 grafts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
0
4

Year Published

2002
2002
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(56 citation statements)
references
References 23 publications
1
51
0
4
Order By: Relevance
“…However, these biomaterials act rather like temporary biologically active wound dressings (Supp & Boyce 2005), providing growth factors, cytokines and ECM for host cells while initiating and regulating wound healing. There are reports of host immunogenic tolerance to allogeneic fibroblasts (Coulomb et al 1998) and their survival in the host up to three weeks (Morimoto et al 2005). Long-term preservation of allogeneic fibroblasts and their proliferation up to two months in the host without signs of immune rejection have also been reported (Sher et al 1983;Bell et al 1984;Eaglstein et al 1999;Hebda & Dohar 1999;Sandulache et al 2003;Griffiths et al 2004).…”
Section: Dermo-epidermal (Composite) Skin Substitutesmentioning
confidence: 96%
“…However, these biomaterials act rather like temporary biologically active wound dressings (Supp & Boyce 2005), providing growth factors, cytokines and ECM for host cells while initiating and regulating wound healing. There are reports of host immunogenic tolerance to allogeneic fibroblasts (Coulomb et al 1998) and their survival in the host up to three weeks (Morimoto et al 2005). Long-term preservation of allogeneic fibroblasts and their proliferation up to two months in the host without signs of immune rejection have also been reported (Sher et al 1983;Bell et al 1984;Eaglstein et al 1999;Hebda & Dohar 1999;Sandulache et al 2003;Griffiths et al 2004).…”
Section: Dermo-epidermal (Composite) Skin Substitutesmentioning
confidence: 96%
“…The main features of radiation skin burns, if compared with thermal burns, are firstly, a very marked dose dependence of the clinical pattern (dry epidermitis (12)(13)(14)(15), moist desquamation (15)(16)(17)(18)(19)(20), and necrosis ( > 25-30 Gy), secondly, the association with a paroxysmal and chronic pain resistant to opiates, and thirdly, the occurrence of uncontrolled successive inflammatory waves during several weeks, months, or years. In all cases, the healing is long, frail, and uncertain.…”
mentioning
confidence: 99%
“…FB has a far-reaching significance in tissueengineered skin. Researches showed that, in in vitro culture, addition of certain amount of FB in collagen gel could enhance the mechanical strength and resistance ability to enzymatic hydrolysis of dermal scaffold 16) . Implanting newborn foreskin FB in nylon net could promote the vascular invasion and growth, and reduce the inflammatory response to nylon and silicone 17) .…”
Section: Discussionmentioning
confidence: 99%